Electrocatalytic Study of the Thin Metallopolymer Film of [2, 2′‐{1, 2‐Ethanediylbis[Nitrilo(1E)‐1‐Ethyl‐1‐Ylidene]}Diphenolate]‐Nickel(II) for Ethanol Electrooxidation. Issue 22 (28th August 2018) - Olean‐Oliveira, André; Pereira, Camila F.; David‐Parra, Diego N.; Teixeira, Marcos F. S.
Abstract: The present paper describes the electrochemical activity of a Ni(II)‐Schiff base metallopolymer electrode for the oxidation of ethanol in alkaline media. The scanning electron microscope results show that the metallopolymer at the glassy carbon surface has a nanoflake‐like lamellar structure, and there is no molecular structural change after treatment with NaOH. Voltammetry measurements indicate that the metallopolymer acts as efficient material for the electrocatalytic oxidation of ethanol, where a high‐valent nickel(IV) was revealed as the reactive intermediate during the anodic scan. An isopotential point can be observed in rotating disk electrode voltammetry for ethanol oxidation. The electrode surface may be considered to consist of two independent electrochemical regions, one corresponding to the ethanol electro‐oxidation by nickel(IV) and the second corresponding to water oxidation. The Tafel slopes were found to be 246 mV dec −1 at low overpotentials and 44 mV dec −1 at high overpotentials, which suggest that the first electron transfer step is the rate controlling step. The specific activity of the metallopolymer‐modified electrode for the ethanol electro‐oxidation reaction was 6.66 mA cm −2 for 0.130 μmol cm −2 of electroactive species of metallopolymer at 0.6 V vs. SCE. Abstract : The activity of a Ni(II)‐Schiff base metallopolymer electrodes for ethanol oxidation is investigated in alkaline media. Tafel slopes of 246 mV dec −1 at low overpotentials and 44 mV dec −1 at high overpotentials are found, suggesting that the first electron transfer step is rate controlling. An isopotential point is observed, revealing that the electrode surface may be considered to consist of two independent electrochemical regions.